Pengaruh Partisipasi Kerja Terhadap Kepuasan Kerja Pegawai Pada PT. Bank BRI Cabang Majene - Fitria, Nur; Nadir, Muhammad; Maghfira, Magfira; Fauzan, Muhammad (Universitas Sulawesi Barat, 2022)
The purpose of this research is to find out whether work participation has an effect on job satisfaction of employees of Bank BRI Majene Branch. Job satisfaction is a person's emotional response to work situations and conditions. In other words, job satisfaction is a set of pleasant or unpleasant employee feelings based on material rewards and psychological (non-material) rewards. The data used in this study is primary data. The sample in this study was 48 people. The data is processed in the form of numerical data (numbers) using a Likert scale. Methods of collecting data by conducting interviews and distributing questionnaires. The data is processed using spss for windows version 21. The data analysis method uses quantitative methods, namely by using simple linear regression analysis. The results of the study prove that the Job Participation Variable has a positive and significant effect on employee job satisfaction at Bank BRI Majene Branch by 51.1% while the rest is influenced by other variables outside this regression equation or variables not examined at 48.9%